APLIKASI ARANG KOMPOS PADA ANAKAN TUSAM - Sri Komarayati; Gusmailina Gusmailina; G Pari (Jurnal Penelitian Hasil Hutan, 2003)
Compost  charcoal  is a  compounded stuff  of  charcoal  and  compost, which is produced  by composting process. The compost charcoal compound products is a new break through in  the composting  techniques as an attempt to improve  the qualitiy of compost.This experiment dealt with the application  of compost  and  compost charcoal to the  Pinus merkusii seedling,  in the greenhouse  for 3 months period.The results revealed that the use of compost alone 30 %  of total media weight could stimulate the growth of Pinus merkusii seedlings to the level of 1 time higher in height ; 7 times  greater in diameter ; 1,5 times  longer in roots length, and 1,5 times heavier biomass in the  dry weight  than those  of control (i.e.  seedlings without compost  treatment). Comparatively,  the corresponding  figures in the use of compost charcoal compound also at 30 % were consecutively 1 time higher  in height ; 2 times greater  in diameter; 1,5 2,6  times longer in root  length and 4,6  6,0 times heavier biomass than the control.The use of compost and charcoal compost both at 30 % of total media weight showed the best effects on the growth of Pinus merkusii seedlings.